Low performance of ultrasound surveillance for the diagnosis of hepatocellular carcinoma in HIV-infected patients. (1st February 2019) - Merchante, Nicolás; Figueruela, Blanca; Rodríguez-Fernández, Miguel; Rodríguez-Arrondo, Francisco; Revollo, Boris; Ibarra, Sofía; Galindo, María J.; Merino, Esperanza; Montero, Marta; Téllez, Francisco; García-Deltoro, Miguel; Rivero-Juárez, Antonio; et al.
Abstract : Objective: To assess the performance of ultrasound surveillance for the diagnosis of hepatocellular carcinoma (HCC) in HIV-infected patients. Methods: The GEHEP-002 cohort recruits HCC cases diagnosed in HIV-infected patients from 32 centers across Spain. The proportion of 'ultrasound lack of detection', defined as HCC diagnosed within the first 3 months after a normal surveillance ultrasound, and the proportion of 'surveillance failure', defined as cases in which surveillance failed to detect HCC at early stage, were assessed. To assess the impact of HIV, a control population of 104 HCC cases diagnosed in hepatitis C virus-monoinfected patients during the study period was used. Results: A total of 186 (54%) out of 346 HCC cases in HIV-infected patients were diagnosed within an ultrasound surveillance program. Ultrasound lack of detection occurred in 16 (8.6%) of them. Ultrasound surveillance failure occurred in 107 (57%) out of 186 cases diagnosed by screening, whereas this occurred in 18 (29%) out of 62 diagnosed in the control group ( P  < 0.0001). HCC cases after ultrasound surveillance failure showed a lower frequency of undetectable HIV viral load at diagnosis. The probability of 1-year and 2-year survival after HCC diagnosis among those diagnosed by screening was 56 and 45% in HIV-infected patients, whereas it was 79 and 64% in HIV-negative patients ( P  = 0.038). Conclusion: The performance of ultrasound surveillance of HCC in HIV-infected patients is very poor and worse than that shown outside HIV infection. A HCC surveillance policy based on ultrasound examinations every 6 months might be insufficient in HIV-infected patients with cirrhosis.